Species Diversity and Chemotypes of Fusarium Species Associated With Maize Stalk Rot in Yunnan Province of Southwest China - Xi, Kaifei; Shan, Liuying; Yang, Yini; Zhang, Guoqing; Zhang, Jun; Guo, Wei (Frontiers in Microbiology, 2021)
Maize stalk rot caused by Fusarium species is one of the most important fungal diseases of maize throughout the world. The disease is responsible for considerable yield losses and has also been associated with mycotoxin contamination of the crop. In this study, a survey of maize stalk rot was performed in seven locations of Yunnan Province in China during the cropping season of 2015 and 2016. Based on morphological and molecular characteristics, 204 isolates belonging to 12 Fusarium spp. from symptomatic stalks of maize were identified. Among the isolated strains, 83 were identified as Fusarium meridionale (40.5 %), 46 as F. boothii (22.5%), 34 as F. temperatum (16.5%), 12 as F. equiseti (5.9%), 10 as F. asiaticum (4.9%), 6 as F. proliferatum (3.0%), 4 as F. verticillioides (2.0%), 4 as F. incarnatum (2.0%), 2 as F. avenaceum (1.0%), 1 as F. cerealis (0.5%), 1 as F. graminearum (0.5%), and 1 as F. cortaderiae (0.5%). F. cortaderiae was the first report on the causal agent of maize stalk rot disease in China. These isolates were divided into five chemotypes: nivalenol (NIV), deoxynivalenol (DON), beauvericin (BEA), zearalenone (ZEN), and fumonisin (FUM). Phylogenetic analysis based on partial sequences of the translation elongation factor (TEF1-α) showed a high degree of interspecific polymorphisms among the isolates. Pathogenicity analysis on maize stalks indicated that all the 12 species of Fusarium were able to cause the disease symptoms with different aggressiveness. This study on population, pathogenicity, and toxigenic chemotypes of Fusarium species associated with maize stalk rot in Yunnan Province of southwest China, will help design an effective integrated control strategy for this disease.